The Effect of Integrity, Competence and Motivation on Job Satisfaction in Mediation by Work Discipline at the Bank Indonesia Representative Office in North Sumatra Province - Mhd. Andy Syahputra Siregar; Isa Indrawan (International Journal of Management, Economic and Accounting, 2024)
This study aims to see the Influence of Integrity, Competence and Motivation on Job Satisfaction in Mediation by Work Discipline at the Bank Indonesia Representative Office in North Sumatra Province, Production factors are needed to produce human output, but without human labor, commodities and services will not provide the same benefits. The results of this study are as follows: Work Discipline has a positive and significant effect on Job Satisfaction with the original sample value of 0.422 and p values of 0.000. Integrity had a positive and significant effect on Work Discipline with the original sample value of 0.358 and p values of 0.000. Integrity had a positive and significant effect on Job Satisfaction with the original sample value of 0.234 and p values of 0.008. Competence had a positive and significant effect on Work Discipline with an original sample value of 0.234 and p values of 0.007. Competence had a positive and insignificant effect on Job Satisfaction with the original sample value of 0.044 and p values of 0.321. Motivation had a positive and significant effect on Work Discipline with the original sample value of 0.394 and p values of 0.000. Motivation had a positive and significant effect on Job Satisfaction with the original sample value of 0.272 and p values of 0.002. Integrity has a positive and significant effect on Job Satisfaction through Work Discipline with an original sample value of 0.155 and p values of 0.003. Competence had a positive and significant effect on Job Satisfaction through Work Discipline with the original sample value of 0.103 and p values of 0.013. Motivation had a positive and significant effect on Job Satisfaction through Work Discipline with the original sample value of 0.170 and p values of 0.004.